Caribbean massive corals not recovering from repeated thermal stress events during 2005–2013. Issue 5 (1st February 2017) - Neal, Benjamin Paul; Khen, Adi; Treibitz, Tali; Beijbom, Oscar; O'Connor, Grace; Coffroth, Mary Alice; Knowlton, Nancy; Kriegman, David; Mitchell, B. Greg; Kline, David I.
Abstract: Massive coral bleaching events associated with high sea surface temperatures are forecast to become more frequent and severe in the future due to climate change. Monitoring colony recovery from bleaching disturbances over multiyear time frames is important for improving predictions of future coral community changes. However, there are currently few multiyear studies describing long‐term outcomes for coral colonies following acute bleaching events. We recorded colony pigmentation and size for bleached and unbleached groups of co‐located conspecifics of three major reef‐building scleractinian corals ( Orbicella franksi, Siderastrea siderea, and Stephanocoenia michelini ; n  = 198 total) in Bocas del Toro, Panama, during the major 2005 bleaching event and then monitored pigmentation status and changes live tissue colony size for 8 years (2005–2013). Corals that were bleached in 2005 demonstrated markedly different response trajectories compared to unbleached colony groups, with extensive live tissue loss for bleached corals of all species following bleaching, with mean live tissue losses per colony 9 months postbleaching of 26.2% (±5.4 SE ) for O. franksi, 35.7% (±4.7 SE ) for S. michelini, and 11.2% (±3.9 SE ) for S. siderea . Two species, O. franksi and S. michelini, later recovered to net positive growth, which continued until a second thermal stress event in 2010. Following this event, all species again lost tissue, with previously unbleached colony species groups experiencing greater declines than conspecific sample groups, which were previously bleached, indicating a possible positive acclimative response. However, despite this beneficial effect for previously bleached corals, all groups experienced substantial net tissue loss between 2005 and 2013, indicating that many important Caribbean reef‐building corals will likely suffer continued tissue loss and may be unable to maintain current benthic coverage when faced with future thermal stress forecast for the region, even with potential benefits from bleaching‐related acclimation. Abstract : Massive coral bleaching events are forecast to become more frequent and severe in the future, but there are currently few multiyear studies describing long‐term outcomes for coral colonies following bleaching, and we do not know how these organisms and ecosystems will respond to a warmer climate. Our study follows a large number of coral colonies in Caribbean Panama for eight years following a major bleaching stress, to monitor resilience and recovery. Although we found some evidence of a possible positive acclimative response, possibly indicating that corals are adapting to rapidly changing conditions, all corals in our study still experienced substantial tissue loss during the study. This indicates that positive acclimation may not be enough for important Caribbean reef‐building corals to survive these disturbances in the long term. Photo credit: D. Kline.